When-definitions revisited - Dziemianko, Anna; Lew, Robert (Oxford Journals, 2013)
The aim of this paper is to analyze the usefulness of when-definitions for conveying information on the grammatical category of headwords. Such definitions are currently employed in some monolingual learners’ dictionaries (MLDs) to define abstract nouns, but they have a much longer tradition in English lexicography. By way of introduction, this defining pattern is compared with other definition formats prevalent in learners’ dictionaries. The research which it has already inspired is then reviewed. The empirical investigation whose results are reported below reveals whether when-definitions actually affect part of speech recognition in most naturalistic conditions. The general evaluation of the real potential of when-definitions to inform users about the syntactic category of nouns leads to recommendations, formulated at the end of the paper, on further implementation of this defining strategy in learners’ dictionaries.
Keywords: definition; folk defining; lexicography; syntactic information; syntax; monolingual dictionary